Lethal brain injury caused by a blank cartridge pistol [Kurusıkı tabancanın neden olduǧu ölümcül kafa travması] - (:unkn) unknown (Ege University Press, 2013)
Blank cartridge guns only fire sound and gas cartridges and have metal barriers to prevent firing of solid projectiles. Their design and sound is very similar to real guns. Therefore, blank cartridge handguns are generally considered as harmless imitations of real guns and they are underestimated in their capacity to inflict serious and potentially life threatening injuries. The aim of this report is to highlight the potential risks of life threating injuries of these guns.
Keywords: Blank carridge; Brain injury; Trauma